This is home : [large type] a novel - Duffy, Lisa, 1970- (Thorndike press large print relationship reads, 2020)
An teenage girl is trying to find her voice and the military wife who moves in downstairs, Quinn Ellis, are united in their search for the true meaning of home. Sixteen-year-old Libby Winters lives in Paradise, a seaside town north of Boston that rarely lives up to its name. After the death of her mother, she lives with her father, Bent, in the middle apartment of their triple decker home, Bent's two sisters, Lucy and Desiree, live on the top floor. A former soldier turned policeman, Bent often works nights, leaving Libby under her aunts' care. Shuffling back and forth between apartments, and the wildly different natures of her family, has Libby wishing for nothing more than a home of her very own. But soon enough, an unlikely friendship begins to blossom, when Libby and Quinn stretch and redefine their definition of family and home.